On the Simplicity of some Cuntz-Pimsner Algebras - Muhly, Paul S.; Solel, Baruch (MATHEMATICA SCANDINAVICA, 1998)
Conditions are given on a C^*-correspondence E over a C^*-algebra that guarantee that the associated Cuntz-Pimsner algebra O (E) is simple. Our findings generalize earlier results of Cuntz[5], Paschke [14], and Boyd, Keswani and Raeburn [2].